PENGGUNAAN MEDIA SOSIAL DAN MARKETPLACE DALAM PENGEMBANGAN USAHA MIE AYAM BAKAR 99, SEMOLOWARU, SURABAYA - Stephanie Astrid Ayu; Citra Anggraini Tresyanto; V. Devina Setyawati; Maria Evangeline Serena Ayu (LPPM Universitas Bina Bangsa, 2023)
Wiith the development of technology and information, media promotion that can be used to expand market share is also growing. Digital marketing is currently also increasingly becoming an attractive platform to be used as a means of promotion. Social media and the marketplace are no longer difficult things to learn in order to be used more optimally to promote SME products. However, due to limited knowledge, assistance from intellectuals is needed to provide education and information about the development of information technology and technology, in particular promotional media through social media and marketplaces. This community service was carried out within (five) 5 months, with the main objective of helping business partners who own Warung Mie Ayam Bakar 99 to promote their products through social media and provide assistance in creating marketplace accounts to expand market share. The end result of this assistance is the promotion of business partners using social media, business partners joining the marketplace, namely shopee food and grab food to make it easier for consumers to make purchases